Cationization of polysaccharides: A path to greener derivatives with many industrial applications - Prado, Héctor J.; Matulewicz, María C. (European polymer journal, 2014)
•Cationic polysaccharides are very useful in a wide range of applications.•This review offers a systematic and up-to-date analysis of the literature.•Modification with dialkylamino hydroxypropyl ethers is covered in detail.•Substitution with other groups is also covered.•Relevant applications of the different products is considered. Cationic polysaccharides are widely used in diverse areas such as water treatment, papermaking, chemical, food, cosmetic, and petroleum industries. The combination of cationic polysaccharides with anionic polymers can lead to interpolyelectrolyte complexes with hydrogel-like structures further expanding the application of the former. The aim of the present review is to fill a gap on the literature about cationization reactions of different polysaccharides and to offer a systematic and up-to-date analysis on the subject. Polysaccharides such as starch, dextran, cellulose and its derivatives, hemicellulose, pectin, chitosan, and seaweed polysaccharides among others are considered. Cationized polysaccharides can be prepared by reaction with various reagents. The main focus is on the substitution with dialkylamino hydroxypropyl and trialkylammonium hydroxypropyl ethers, being that the most common modifications involve the introduction of the 2-hydroxy-3-(trimethylammonium)propyl group by reaction of the polysaccharide with 2,3-epoxypropyltrimethylammonium chloride in an alkaline solution. An alternative to this method involves generation of the reagent in situ from 3-chloro-2-hydroxypropyltrimethylammonium chloride. In addition, polysaccharides substituted with other type of cationic groups and amphoteric derivatives are presented. Different methods of analysis, toxicological studies and applications of the modified polymers are also included.